(untitled) (Polish Yearbook of International Law, 2021)
The article concerns the obligations to negotiate and conclude agreements in good faith (pactum de negotiando and pactum de contrahendo), which are used in international legal practice to more efficiently settle disputes or negotiate new agreements in various areas of international law. These obligations, however, are sometimes mixed together and misunderstood. They also give rise to various interpretation disputes related to their existence as obligations and their content. The aim of the study is to show that these are not simple obligations, but bundles of obligations. Such perception of them makes it possible to distinguish both pacta and penetrate into their rich content, as well as to unequivocally apply to their performance the principle of performing international obligations in good faith (Art. 2(2) of the UN Charter), especially in the form of pacta sunt servanda (Art. 26 of the Vienna Convention on the Law of Treaties).